KONTEN MATERI KIMIA DALAM STANDAR ISI PEMBELAJARAN IPA SMP BERDASARKAN K-13 - oktariani oktariani; Asyti Febliza; Yelfira Sari (UIR Press, 2020)
Static achievement of Indonesian students in TIMSS, of course requires improvement efforts. One of the improvement efforts can be done by conducting further studies related to the results of Indonesia's achievements in TIMSS. The aim of this study to describe the chemistry content and the of science learning in junior high school based on K-13. This research is a descriptive study with content analysis method. Content analysis was carried out on documents related to K-13 specifically the content standards, the learning process, syllabus and science textbooks of junior high school. The results showed that there are chemistry contents in science learning of junior high school. The chemistry contents contained in science learning of junior high school is divided into 6 main subjects and 5 demands of cognitive abilities, namely C1, C2, C3, C4 and C6, while the demands of cognitive ability C5 (evaluating) are not contained in the Chemistry content in science learning of junior high school . Key words: chemistry content, cognitive demands abilities, K-13, science learning